Dinamika Peran Usaha Tambak Udang dalam Meningkatkan Perekonomian Masyarakat : (Di Desa Pagar Jaya, Kec. Punduh Pidada, Kabupaten Pesawaran. Lampung) - Zaki, Muhammad Akmal; Dino Ananda; Maya Jiva Suara; Elsa Sari; Vera Meirani; Sindy Amelia; Alief Rakhman Setyanto (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The role of shrimp farming in increasing community income is very important, especially in coastal areas. One of the businesses that are quite widely run in this area is the fisheries sector. The study aims to determine the role of shrimp farming in improving the community's economy, in Jaya Tani Hamlet, Pagar Jaya Village. Punduh Pidada District, Pesawaran Lampung. This study uses a qualitative descriptive method. The sources used are primary and secondary data. The data collection techniques were obtained from interviews, observations, and journals. The results of the study showed that the Benuangan 1 shrimp pond had a positive impact on improving the community's economy. Therefore, it is hoped that the owners and managers of the Benuangan 1 shrimp pond must continue to maintain the provision of salaries and bonuses in accordance with the responsibilities of each worker in this pond.